ANALISIS EFEK KEBIJAKAN DIVIDEN DAN KINERJA KEUANGAN TERHADAPPERUSAHAAN PADA KOPERASI CU. DOSNITAHI PINANG SORI KABUPATENTAPANULI TENGAH - Indah Sari Pasaribu; Yenni Sofiana Tambunan; Safriadi Pohan (Universitas Sains dan Teknologi Komputer, 2022)
Analysis of the effect of dividend policy and financial performance on firm value in CU Cooperatives. Dosnitahi Pinang Sori Central Tapanuli Regency: Company Management Study Program at STIE Al Washliyah. This study aims to determine the effect of dividend policy and financial performance on firm value in CU Cooperatives. Dosnitahi Pinang Sori, Central Tapanuli Regency. The type of research used in this research is descriptive quantitative research, because this research method aims to obtain information by making a picture or description of what is or is happening. This research was conducted from April 14 to September 2022. For this research the population is 57 people. The population is taken from all CU Cooperative employees. Dosnitahi Pinang Sori, Central Tapanuli Regency. because the population is below 100 people, the authors take the entire population meeting to be used as a sample of 57 people. The type of data used in this thesis research is the type of subject data and primary data sources. The research data is normally distributed because on the bell-shaped histogram graph, on the P-P plot above, you can see the distribution of the data close to the diagonal line and the Kolmogorov-Smirnov statistical test results show a sig value of 0.200, this means that the sig value is greater than 0.05 which means that all data used in this study are normally distributed). The results of the multiple regression test obtained Y = 4.885 + 5.056 X1 - .701 X2 . this means that the influence of the dependent variable (firm value) is determined by the independent variable (dividend policy and financial performance) with a regression coefficient of 5.056 and -.701. where if one unit of variable X or a certain value is added, the variable Y (company value) will also increase multiplied by that certain value. From the results of data testing, the results obtained are t count <t table, so Ha is accepted and H0 is rejected. Based on this, the hypothesis proposed in this study is accepted